Accounting information systems user’s satisfaction among accounts preparer / Mohamad Azmi Nias Ahmad and Sharir Aizat Abdul Ghani - Mohamad Azmi Nias Ahmad; Sharir Aizat Abdul Ghani (Faculty of Business Management, 2013)
This paper aims to analyze various studies in order to develop an instrument to measure Accounting Information Systems (AIS) user’s satisfaction instruments. The aim is to compare and analyzes which attributes uses in measuring computer user satisfaction. Four peer-reviewed empirical journals were analyzed.